Long-acting anti-oxidation solution for ultra-thin electrolytic copper foil and preparation method and application thereof
Patent Information
- Application Number
- CN202611100977.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]有鉴于此,本发明提供了一种用于极薄电解铜箔的长效防氧化液及其制备方法与应用,以解决现有防氧化液耐热性与持久性差,易致极薄铜箔褶皱断带、成膜不均,且残留影响结合力的问题
1、本发明所述用于极薄电解铜箔的长效防氧化液以2-氨基-5-巯基-1,3,4-噻二唑为主成膜剂,其自身具有高分解温度,为后续在铜箔表面形成的防护膜层提供了耐热基础;交联剂能够通过化学交联将主成膜剂分子连接成三维网络结构,显著提高了防护膜层的热分解活化能;抗氧化剂在高温初期优先消耗氧自由基,为铜箔表面提供了热氧缓冲;三者共同构成“网络骨架-热氧缓冲-自由基捕捉”的协同耐热体系,有效解决了现有防氧化液耐热性不足的技术问题;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-oxidation technology for electrolytic copper foil, and in particular to a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil, its preparation method, and its application. Background Technology
[0002] With the rapid development of 5G communication, new energy vehicles, and high-end consumer electronics industries, the performance requirements for printed circuit boards and lithium-ion batteries are becoming increasingly stringent. Electrolytic copper foil, as its core basic material, is developing towards ultra-thinness (thickness ≤ 6 μm, or even below 4.5 μm), high elongation, high tensile strength, and high heat resistance.
[0003] After manufacturing, ultra-thin electrolytic copper foil has a highly chemically active surface that readily reacts with oxygen and moisture in the air at room temperature to form copper oxides (such as CuO and Cu2O), causing surface discoloration (yellowing or darkening) and severely affecting its conductivity, solderability, and the adhesion of subsequent coatings. Therefore, it is essential to perform anti-oxidation treatment on its surface.
[0004] Existing mainstream anti-oxidation technologies are mainly divided into two categories: one is chromate passivation, which has good anti-oxidation performance, but hexavalent chromium is highly toxic and carcinogenic, seriously violating environmental regulations; the other is chromium-free organic / inorganic composite systems (such as benzotriazole BTA and its derivatives combined with phosphate), which, although environmentally friendly, has significant technical problems when applied to extremely thin copper foils: during subsequent lamination, welding, or lithium battery electrode baking (commonly above 200°C), the organic film layer decomposes and volatilizes, causing the copper foil to oxidize and discolor rapidly at high temperatures, resulting in poor heat resistance. The protective film layer is not dense enough, and under normal storage environment (high temperature and high humidity), oxidation spots will appear within a few weeks to a few months, resulting in poor anti-oxidation durability. The ultra-thin copper foil has low rigidity, is easy to wrinkle and tear, and the existing anti-oxidation liquid has high surface tension and poor compatibility with the ultra-thin substrate, resulting in wrinkles, pinholes and even breakage on the foil surface. At the same time, the existing anti-oxidation liquid has poor wetting and spreading uniformity on the copper foil surface, resulting in inconsistent anti-oxidation effect. Moreover, some anti-oxidation liquid remains on the foil surface, affecting the subsequent interfacial bonding with resin (PCB) or negative electrode active material (battery).
[0005] Therefore, it is of great significance to develop an anti-oxidation solution that is environmentally friendly, high-temperature resistant, provides long-lasting protection, and is adapted to the mechanical properties of extremely thin electrolytic copper foil. Summary of the Invention
[0006] In view of this, the present invention provides a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil, its preparation method and application, to solve the problems of poor heat resistance and durability of existing anti-oxidation solutions, which easily cause wrinkles and breakage of ultra-thin copper foil, uneven film formation, and residues that affect adhesion.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil, comprising the following components by mass percentage: 2-Amino-5-mercapto-1,3,4-thiadiazole 0.5~2.0%, crosslinking agent 0.1~0.8%, antioxidant 0.05~0.3%, amino-modified nano silica 0.05~0.5%, wetting and leveling agent 0.01~0.1%, cosolvent 0.8~2.5%, balance is water.
[0008] Preferably, the long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil further includes a pH adjuster, wherein the amount of the pH adjuster is such that the pH of the long-lasting anti-oxidation solution is 6.5 to 7.5.
[0009] Preferably, the pH adjuster includes one or more of citric acid, formic acid, acetic acid, propionic acid, and lactic acid.
[0010] Preferably, the crosslinking agent includes one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane.
[0011] Preferably, the antioxidant includes one or more of propyl gallate, tea polyphenols, and tert-butylhydroquinone.
[0012] Preferably, the wetting and leveling agent includes one or more of the following: TF-310 fluorocarbon surfactant, FEO-300 fluorocarbon surfactant, FEO-500 fluorocarbon surfactant, Surflon S-242 fluorocarbon surfactant, and MEGAFACE F-477 fluorocarbon surfactant.
[0013] Preferably, the co-solvent includes one or more of triethanolamine, diethanolamine, monoethanolamine, and aminomethylpropanol.
[0014] The present invention also provides a method for preparing the above-mentioned long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil, comprising the following steps: 1) Mix 2-amino-5-mercapto-1,3,4-thiadiazole with a co-solvent and some water to obtain a mixed solution; 2) Mix the mixed solution, crosslinking agent, antioxidant, amino-modified nano silica, wetting and leveling agent, residual water and pH adjuster, and then ultrasonically disperse them to obtain a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil.
[0015] Preferably, the mixing temperature in step 1) is 60~80℃; the mass ratio of the partial water in step 1) to the remaining water in step 2) is 1~3:1~4; the ultrasonic dispersion power in step 2) is 200~300 W, and the time is 10~60 min.
[0016] The present invention also provides an application of the long-lasting anti-oxidation solution prepared by the above-described method for preparing long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil in the anti-oxidation of ultra-thin electrolytic copper foil.
[0017] As can be seen from the above technical solution, compared with the prior art, the beneficial effects of the present invention are as follows: 1. The long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil of the present invention uses 2-amino-5-mercapto-1,3,4-thiadiazole as the main film-forming agent, which has a high decomposition temperature, providing a heat-resistant basis for the protective film layer subsequently formed on the copper foil surface; the crosslinking agent can connect the main film-forming agent molecules into a three-dimensional network structure through chemical crosslinking, which significantly improves the thermal decomposition activation energy of the protective film layer; the antioxidant preferentially consumes oxygen free radicals in the early stage of high temperature, providing a thermal-oxygen buffer for the copper foil surface; the three together constitute a synergistic heat-resistant system of "network skeleton-thermal-oxygen buffer-free radical capture", which effectively solves the technical problem of insufficient heat resistance of existing anti-oxidation solutions; 2. The long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil of this invention also contains a wetting and leveling agent, amino-modified nano-silica, and a co-solvent. The wetting and leveling agent reduces the dynamic surface tension of the anti-oxidation solution, ensuring instantaneous super-spreading on the hydrophobic surface of the ultra-thin electrolytic copper foil. The co-solvent enables the main film-forming agent to form a soluble ammonium salt, which, combined with a subsequent acidic pH adjuster, allows the main film-forming agent to precipitate uniformly as fine particles. Simultaneously, the amino-modified nano-silica, rich in amino groups, can form hydrogen bonds or chemical bonds with the crosslinking agent, anchoring and uniformly dispersing the precipitated main film-forming agent particles in the liquid phase, preventing aggregation and precipitation. In summary, the long-lasting anti-oxidation solution of this invention, through the triple synergy of "ultra-low surface tension wetting - uniform precipitation of fine particles - nano-silica anchoring and dispersion," significantly reduces the risk of wrinkles, pinholes, and breakage of ultra-thin copper foil during the coating process, achieving the formation of a uniform, dense, high-quality protective film on the surface of ultra-thin electrolytic copper foil. 3. Traditional anti-oxidation films are inert physical coatings, while this invention, by adding a crosslinking agent, allows the hydrolyzable ethoxy / methoxy group at one end to bond with the hydroxyl groups on the copper foil surface, while the exposed amino or epoxy groups at the other end can undergo crosslinking reactions with subsequent organic materials, thus transforming the traditional inert anti-oxidation film into an active bonding layer. At the same time, the amino groups on the surface of the amino-modified nano-silica also participate in this interfacial bonding network, further enhancing the interfacial bonding strength, thereby turning "contamination residue" into a "favorable interface" and fundamentally solving the compatibility contradiction between anti-oxidation treatment and subsequent processing. 4. After treating ultra-thin electrolytic copper foil with the long-lasting anti-oxidation solution described in this invention, no oxidation phenomenon was observed after standing at room temperature for 25 days, and no oxidation phenomenon was observed after standing at a high temperature of 240℃ for 1 hour. This indicates that the anti-oxidation solution described in this invention has excellent long-lasting anti-oxidation performance and heat resistance. At the same time, the long-lasting anti-oxidation solution described in this invention is chromium-free, has good environmental friendliness and industrial applicability, and is suitable for industrial continuous production applications. Detailed Implementation
[0018] This invention provides a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil, preferably comprising the following components in the following mass percentages: 0.5-2.0% 2-amino-5-mercapto-1,3,4-thiadiazole, 0.1-0.8% crosslinking agent, 0.05-0.3% antioxidant, 0.05-0.5% amino-modified nano-silica, 0.01-0.1% wetting and leveling agent, 0.8-2.5% cosolvent, and the balance being water. More preferably, it comprises the following components in the following mass percentages: 0.8-1.8% 2-amino-5-mercapto-1,3,4-thiadiazole, crosslinking agent, and cosolvent. The composition comprises: 0.2-0.7% of an agent, 0.1-0.25% of an antioxidant, 0.15-0.4% of an amino-modified nano-silica, 0.02-0.08% of a wetting and leveling agent, 1-2% of a cosolvent, and the balance being water. More preferably, it comprises the following components by mass percentage: 1-1.5% of 2-amino-5-mercapto-1,3,4-thiadiazole, 0.3-0.5% of a crosslinking agent, 0.15-0.2% of an antioxidant, 0.2-0.3% of an amino-modified nano-silica, 0.03-0.05% of a wetting and leveling agent, 1.2-1.5% of a cosolvent, and the balance being water.
[0019] In this invention, the long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil preferably includes a pH adjuster, wherein the amount of the pH adjuster is such that the pH of the long-lasting anti-oxidation solution is 6.5 to 7.5, preferably 6.8 to 7.2, and more preferably 7.
[0020] In this invention, the pH adjuster preferably includes one or more of citric acid, formic acid, acetic acid, propionic acid, and lactic acid.
[0021] In this invention, the crosslinking agent preferably includes one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane.
[0022] In this invention, the antioxidant preferably includes one or more of propyl gallate, tea polyphenols, and tert-butylhydroquinone.
[0023] In this invention, the wetting and leveling agent preferably includes one or more of the following: TF-310 fluorocarbon surfactant, FEO-300 fluorocarbon surfactant, FEO-500 fluorocarbon surfactant, Surflon S-242 fluorocarbon surfactant, and MEGAFACE F-477 fluorocarbon surfactant.
[0024] In this invention, the cosolvent preferably includes one or more of triethanolamine, diethanolamine, monoethanolamine, and aminomethylpropanol.
[0025] The present invention also provides a method for preparing the above-mentioned long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil, comprising the following steps: 1) Mix 2-amino-5-mercapto-1,3,4-thiadiazole with a co-solvent and some water to obtain a mixed solution; 2) Mix the mixed solution, crosslinking agent, antioxidant, amino-modified nano silica, wetting and leveling agent, residual water and pH adjuster, and then ultrasonically disperse them to obtain a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil.
[0026] In this invention, the mixing temperature in step 1) is 60~80℃, preferably 65~75℃, more preferably 70℃; the mass ratio of the partial water in step 1) to the remaining water in step 2) is 1~3:1~4, preferably 1.2~2.8:1.2~3.5, further preferably 1.4~2.5:1.5~3, more preferably 1.5~2:2~2.5; the ultrasonic dispersion power in step 2) is 200~300 W, preferably 220~280 W, further preferably 230~260 W, more preferably 250 W; the ultrasonic dispersion time is 10~60 min, preferably 15~50 min, further preferably 20~40 min, more preferably 30~35 min.
[0027] The present invention also provides an application of the long-lasting anti-oxidation solution prepared by the above-described method for preparing long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil in the anti-oxidation of ultra-thin electrolytic copper foil.
[0028] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0029] Example 1
[0030] In this embodiment, the long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil comprises the following components by mass percentage: 0.5% 2-amino-5-mercapto-1,3,4-thiadiazole, 0.1% γ-aminopropyltriethoxysilane, 0.05% propyl gallate, 0.05% amino-modified nano silica, 0.01% TF-310 fluorocarbon surfactant, 0.8% triethanolamine, and the balance being water; The preparation method of the above-mentioned long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil is as follows: 1) 2-Amino-5-mercapto-1,3,4-thiadiazole was mixed with triethanolamine and a portion of water at 60°C to obtain a mixed solution; 2) Mix the mixed solution, γ-aminopropyltriethoxysilane, propyl gallate, amino-modified nano silica, TF-310 fluorocarbon surfactant, remaining water and citric acid (the mass ratio of partial water to remaining water is 1:4), and ultrasonically disperse at 200 W for 50 min to obtain a long-lasting anti-oxidation solution with a pH of 6.5 for ultra-thin electrolytic copper foil.
[0031] Example 2
[0032] In this embodiment, the long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil comprises the following components by mass percentage: 1.5% 2-amino-5-mercapto-1,3,4-thiadiazole, 0.4% γ-aminopropyltrimethoxysilane, 0.2% tea polyphenols, 0.25% amino-modified nano silica, 0.04% FEO-300 fluorocarbon surfactant, 1.3% triethanolamine, and the balance being water; The preparation method of the above-mentioned long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil is as follows: 1) Mix 2-amino-5-mercapto-1,3,4-thiadiazole with triethanolamine and a portion of water at 70°C to obtain a mixed solution; 2) Mix the mixed solution, γ-aminopropyltrimethoxysilane, tea polyphenols, amino-modified nano silica, FEO-300 fluorocarbon surfactant, remaining water and acetic acid (the mass ratio of part water to remaining water is 1:2), and ultrasonically disperse at 250 W for 35 min to obtain a long-lasting anti-oxidation solution with a pH of 7 for ultra-thin electrolytic copper foil.
[0033] Example 3
[0034] In this embodiment, the long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil comprises the following components by mass percentage: 2-amino-5-mercapto-1,3,4-thiadiazole 2.0%, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane 0.8%, tert-butylhydroquinone 0.3%, amino-modified nano silica 0.5%, FEO-500 fluorocarbon surfactant 0.1%, aminomethylpropanol 2.5%, and the balance being water; The preparation method of the above-mentioned long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil is as follows: 1) Mix 2-amino-5-mercapto-1,3,4-thiadiazole with aminomethylpropanol and a portion of water at 80°C to obtain a mixed solution; 2) Mix the mixed solution, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, tert-butylhydroquinone, amino-modified nano-silica, FEO-500 fluorocarbon surfactant, remaining water and propionic acid (the mass ratio of partial water to remaining water is 2:1), and ultrasonically disperse at 300 W for 10 min to obtain a long-lasting anti-oxidation solution with a pH of 7 for ultra-thin electrolytic copper foil.
[0035] Comparative Example 1
[0036] The only difference between this comparative example and Example 1 is that the crosslinking agent γ-aminopropyltriethoxysilane was not added; all other components and preparation conditions remained the same.
[0037] Comparative Example 2
[0038] The only difference between this comparative example and Example 2 is that amino-modified nano-silica was not added; all other components and preparation conditions remained the same.
[0039] Comparative Example 3
[0040] The only difference between this comparative example and Example 2 is that the cosolvent triethanolamine was not added; all other components and preparation conditions remained the same.
[0041] Comparative Example 4
[0042] The only difference between this comparative example and Example 3 is that the temperature in step 1) is set to 25°C, while the other components and preparation conditions remain unchanged.
[0043] Application Example 1
[0044] A 5.5 μm thick electrolytic copper foil was peeled off from the cathode roller by a peeling shaft. The foil was then completely immersed in the long-lasting anti-oxidation solution prepared in Example 1 by a guide roller at a temperature of 32°C for 8 seconds. The foil was then squeezed dry by an extrusion roller, dried by hot air at 130°C, wound up, and slit to obtain an ultra-thin electrolytic copper foil without wrinkles, pinholes, or breaks.
[0045] Application Example 2
[0046] The only difference between this application example and application example 1 is that the long-lasting antioxidant solution is replaced with the long-lasting antioxidant solution prepared in example 2.
[0047] Application Example 3
[0048] The only difference between this application example and application example 1 is that the long-lasting antioxidant solution is replaced with the long-lasting antioxidant solution prepared in example 3.
[0049] Application Example 4
[0050] The only difference between this application example and application example 1 is that the long-lasting antioxidant solution is replaced with the long-lasting antioxidant solution prepared in comparative example 1.
[0051] Application Example 5
[0052] The only difference between this application example and application example 1 is that the long-lasting antioxidant solution is replaced with the long-lasting antioxidant solution prepared in comparative example 2.
[0053] Application Example 6
[0054] The only difference between this application example and application example 1 is that the long-lasting antioxidant solution is replaced with the long-lasting antioxidant solution prepared in comparative example 3.
[0055] Application Example 7
[0056] The only difference between this application example and application example 1 is that the long-lasting antioxidant solution is replaced with the long-lasting antioxidant solution prepared in comparative example 4.
[0057] Application Example 8
[0058] The only difference between this application example and application example 1 is that the copper foil was not immersed in a long-lasting anti-oxidation solution for anti-oxidation treatment.
[0059] The long-lasting anti-oxidation solutions prepared in Examples 1-3 and Comparative Examples 1-4 for anti-oxidation of ultra-thin electrolytic copper foils were used in Application Examples 1-7 above. The resulting ultra-thin electrolytic copper foils were then subjected to room temperature oxidation resistance, heat resistance, and peel strength tests. Specifically, the room temperature oxidation resistance of a 150 mm × 150 mm finished ultra-thin electrolytic copper foil was tested at 30°C and 80% relative humidity; the heat resistance of a 150 mm × 150 mm finished ultra-thin electrolytic copper foil was tested at a constant temperature of 240°C; and the peel strength of a 10 mm × 100 mm finished ultra-thin electrolytic copper foil was tested according to IPC-TM-6502.4.8. The results are shown in Table 1.
[0060] Table 1 Performance test results of finished ultra-thin electrolytic copper foil
[0061] As shown in Table 1, the ultra-thin electrolytic copper foils treated with the anti-oxidation solutions prepared in Examples 1-3 of this invention (Application Examples 1-3) showed no oxidation or discoloration in the room temperature oxidation resistance (30℃×120h and 600h) and heat resistance (240℃×1h) tests. Furthermore, they exhibited high peel strength, significantly superior to the untreated sample (Application Example 8, peel strength 0.79 N / mm) and the samples using Comparative Examples 1-4. This demonstrates that the anti-oxidation solution described in this invention can impart excellent long-term room temperature oxidation resistance, high-temperature heat stability, and good interfacial adhesion to the ultra-thin electrolytic copper foils.
[0062] Further analysis revealed that the copper foil in Comparative Example 1, without crosslinking agent treatment, exhibited significant discoloration and spotting in both room temperature oxidation resistance and heat resistance tests, with its peel strength decreasing to 0.81 N / mm. This indicates that the absence of crosslinking agent prevented the formation of a three-dimensional network structure in the anti-oxidation film, resulting in a significant decrease in film density and thermal stability, as well as a substantial reduction in interfacial adhesion. In Comparative Example 2, the copper foil without amino-modified nano-silica treatment showed slight darkening and spotting in both room temperature and heat resistance tests, with a peel strength of 0.82 N / mm, still significantly inferior to the example. This suggests that the absence of amino-modified nano-silica weakened the anchoring and dispersion effect of the main film-forming agent particles, reducing film uniformity and density, thus affecting protective performance and adhesion. Similarly, the copper foil in Comparative Example 3, without co-solvent treatment, also showed slight darkening and spotting, with a peel strength of 0.86 N / mm. The N / mm value indicates that the lack of a co-solvent prevents the main film-forming agent from fully dissolving and uniformly precipitating, resulting in poor dispersion of the main film-forming agent in the anti-oxidation solution, reduced film quality, and consequently affecting the anti-oxidation effect and interfacial bonding strength. In Comparative Example 4, the main film-forming agent was dissolved without heating, only mixed at room temperature, and the treated copper foil also showed slight darkening and spots, with a peel strength of 0.87 N / mm. This indicates that heating conditions are crucial for the main film-forming agent and co-solvent to fully react and form soluble ammonium salts, achieving subsequent uniform precipitation. Insufficient dissolution of the main film-forming agent at room temperature leads to a decrease in the performance of the anti-oxidation solution.
[0063] The blank sample (Application Example 8) without anti-oxidation treatment showed severe discoloration and large-area patches in all tests, and had the lowest peel strength (0.79 N / mm), confirming the necessity of anti-oxidation treatment for ultra-thin electrolytic copper foil.
[0064] In summary, the anti-oxidation liquid provided by this invention, through the synergistic combination of 2-amino-5-mercapto-1,3,4-thiadiazole, crosslinking agent, antioxidant, amino-modified nano-silica, wetting and leveling agent, co-solvent, and pH adjuster, combined with a heating-dissolving-ultrasonic dispersion preparation process, can form a uniform, dense, heat-resistant, and strongly interfacially bonded anti-oxidation film layer on the surface of extremely thin electrolytic copper foil. This effectively solves the problems of insufficient heat resistance, poor adaptability, uneven film formation, and poor interfacial compatibility in existing technologies, and has a very broad application prospect.
[0065] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil, characterized in that, The components include the following mass percentages: 2-Amino-5-mercapto-1,3,4-thiadiazole 0.5~2.0%, crosslinking agent 0.1~0.8%, antioxidant 0.05~0.3%, amino-modified nano silica 0.05~0.5%, wetting and leveling agent 0.01~0.1%, cosolvent 0.8~2.5%, balance is water.
2. The long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil according to claim 1, characterized in that, It also includes a pH adjuster, the amount of which is used to make the pH of the long-lasting antioxidant solution 6.5 to 7.
5.
3. The long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil according to claim 2, characterized in that, The pH adjuster includes one or more of citric acid, formic acid, acetic acid, propionic acid, and lactic acid.
4. A long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil according to any one of claims 1 to 3, characterized in that, The crosslinking agent includes one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane.
5. The long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil according to claim 4, characterized in that, The antioxidants include one or more of propyl gallate, tea polyphenols, and tert-butylhydroquinone.
6. The long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil according to claim 5, characterized in that, The wetting and leveling agent includes one or more of the following: TF-310 fluorocarbon surfactant, FEO-300 fluorocarbon surfactant, FEO-500 fluorocarbon surfactant, Surflon S-242 fluorocarbon surfactant, and MEGAFACE F-477 fluorocarbon surfactant.
7. The long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil according to claim 6, characterized in that, The cosolvent includes one or more of triethanolamine, diethanolamine, monoethanolamine, and aminomethylpropanol.
8. A method for preparing a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil according to any one of claims 1 to 7, characterized in that, Includes the following steps: 1) Mix 2-amino-5-mercapto-1,3,4-thiadiazole with a co-solvent and some water to obtain a mixed solution; 2) Mix the mixed solution, crosslinking agent, antioxidant, amino-modified nano silica, wetting and leveling agent, residual water and pH adjuster, and then ultrasonically disperse them to obtain a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil.
9. A method for preparing a long-lasting anti-oxidation solution for ultra-thin electrolytic copper foil according to claim 8, characterized in that, The mixing temperature in step 1) is 60~80℃; The mass ratio of the water in step 1) to the remaining water in step 2) is 1~3:1~4; The ultrasonic dispersion described in step 2) has a power of 200~300 W and a time of 10~60 min.
10. The application of the long-lasting anti-oxidation solution prepared by the method of any one of claims 8 to 9 in the anti-oxidation of ultra-thin electrolytic copper foil.